Optimalisasi Sistem Chatbot Layanan Pelanggan E-Commerce melalui Kombinasi Rule-Based dan Algoritma K-Nearest Neighbor (KNN) - Zaenal Mustofa; Febryantahanuji Febryantahanuji; Arsito Ari Kuncoro (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to design and evaluate a hybrid chatbot prototype that combines a rule-based approach with the K-Nearest Neighbor (KNN) algorithm to classify customer satisfaction levels. This system was developed as an automated customer service solution for the e-commerce sector, which demands speed, efficiency, and personalization. By using numerical features such as information comprehension (X1), chatbot rating (X2), and conversation duration (X3), the KNN algorithm determines whether a user is satisfied or not after an interaction session. The classification results indicate that some